2005
DOI: 10.1016/j.polymdegradstab.2005.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Fire retardancy of vinyl ester nanocomposites: Synergy with phosphorus-based fire retardants

Abstract: This paper is NOT THE PUBLISHED VERSION; but the author's final, peer-reviewed manuscript. The published version may be accessed by following the link in the citation below.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
49
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(55 citation statements)
references
References 19 publications
3
49
0
Order By: Relevance
“…The thermogravimetric and cone calorimetry analyses indicated that PNC and PS had similar degradation onset and the pathway, thus MAG is not a flame retardant for PS. This conclusion was found also applicable to PNCs based on thermoset vinyl ester, 162 or to EVAc. 163 Morgan et al 164 prepared a series of EVAc-based PNCs with 5 wt% of MAG, pre-intercalated with inorganic (H þ ,N a þ ,C a 2þ ,M g 2þ ) and organic (2M2HTA þ ) cations.…”
Section: Pnc With Synthetic Magadiite (Mag)supporting
confidence: 56%
“…The thermogravimetric and cone calorimetry analyses indicated that PNC and PS had similar degradation onset and the pathway, thus MAG is not a flame retardant for PS. This conclusion was found also applicable to PNCs based on thermoset vinyl ester, 162 or to EVAc. 163 Morgan et al 164 prepared a series of EVAc-based PNCs with 5 wt% of MAG, pre-intercalated with inorganic (H þ ,N a þ ,C a 2þ ,M g 2þ ) and organic (2M2HTA þ ) cations.…”
Section: Pnc With Synthetic Magadiite (Mag)supporting
confidence: 56%
“…The systems that has been investigated, MMT with bromine [8], with phosphorus [29], and with mineral plus LDH with APP [16] and melamine [17], have been seen to be effective but the ZnAl LDH shows no positive interactions with conventional fire retardants in PE. Further work will be necessary to determine the cause of this behavior.…”
mentioning
confidence: 99%
“…The use of double-layered hydroxides is an alternative to the use of cationic clays for making epoxy-based composites with good fire properties [Ibeh et al (2006)]. The cone calorimeter results on vinylesters containing clays (Cloisite 15 A) or POSS highlighted a reduction of maximum heat release rate and increase of time to ignition, but no modification on total heat released [Chigwada et al (2005)]. A combination with a phosphorus-based flame retardant promotes a greater improvement.…”
Section: Modification Of Gas Diffusion Propertiesmentioning
confidence: 99%